Pandemic impact on the co-movement and hedging effectiveness of the global futures markets - Zainudin, Ahmad Danial; Mohamad, Azhar (Taylor & Francis, 2023)
This paper examines the impact of COVID-19 on five of the world’s most liquid futures markets. The results of our wavelet coherence analysis for spot futures reveal two important findings. First, spot futures coherence movements during the pandemic period are influential at both low and high frequency scales. Second, the spectrogram shows mixed causality directions at all scales of observation in the period before and during the pandemic. In terms of hedging effectiveness, OLS and VECM show improvements in hedging effectiveness. Nevertheless, multiscale analysis with wavelet methods shows that hedging effectiveness depends on the hedge period due to the instability of the spot-futures association during the pandemic period. Our results refute the conventional wisdom among finance scholars that a stronger link between spot and futures markets during the crisis improves hedging effectiveness. We would emphasise that investment baskets and hedge pairs should be reviewed frequently to optimise results.